Social Stigma towards Health Care Workers during COVID Pandemic : A Hospital based Cross-sectional Study in Kolkata - Ripan Saha; Vineeta Shukla; Ankita Mishra; Meghna Mukherjee; Mausumi Basu; Raghunath Misra (Indian Association of Preventive and Social Medicine, 2021)
Introduction: With the rise of COVID-19 pandemic, the health staffs have faced resistance and disrespect by the society. They have been stigmatised unnecessarily that has been resulted from fear and poor knowledge of general population regarding spread of COVID-19 infection. Objective: To estimate the proportion of health care workers whoexperienced social stigma during COVID 19 pandemic and to determine the association of social stigma with their socio-demographic and other background characteristics. Method: A descriptive type of observational study, cross-sectional in design was carried out amonghealth care workers(HCWs) of a tertiary care hospital in Kolkataduring the COVID-19 lockdown period (19th May 2020- 20th July 2020) using a pre-designed, pre-tested, structured schedule. By simple random sampling, 422 HCWs were selected and 410 of them had given consent to participate in this study. MS Excel 2010 and SPSS v20.0 were used for data entry and binary logistic regression. Results: About 52.68 % had experienced 'Significant Social Stigma', 32.92% experienced 'Insignificant Social Stigma' and only 14.39% had 'no stigma'. Age groups of 25-40years and mode of transport by hospital vehicle had significant association with social stigma.Conclusion: More than half of the study population experienced "Significant Social Stigma". The HCWs who were travelling by hospital vehicles from home to attend their duties and HCWs of younger age group were stigmatised in different ways.